Broiler breeder feed treatment with a formaldehyde-based sanitizer and its consequences on reproduction, feed and egg contamination, and offspring livability - Luis P. Avila; Kelly M. Sweeney; Cheryl Schaeffer; Nicole Holcombe; Callie Selby; Enrique Montiel; Jeanna L. Wilson (Journal of Applied Poultry Research, 2023)
SUMMARY: Due to increased demand for broiler chicks, broiler breeder operations are interested in dietary and feeding strategies that can enhance broiler breeder reproduction and improve hatchability. Microbial contamination of fertile breeder eggs can be detrimental to hatchability and broiler chick growth performance. Formaldehyde and organic acids have been used to sanitize layer feed to reduce the contamination of table eggs. Broiler breeder feed sanitation is a practice that needs further exploration as it could improve breeder performance and offspring livability. The objectives of this experiment were to evaluate the effect of a formaldehyde-based feed sanitizer on broiler breeder hen reproduction, feed and eggshell contamination, incubation characteristics, and offspring early livability. Treating broiler breeder feed did not affect overall hen reproduction or hatchability, although it reduced live pip numbers at hatch, and improved the graded quality of hatched chicks. Treated feed showed less presumptive aerobic bacteria, fungus, C. perfringens, and Enterobacteriaceae compared to nontreated (control) feeds. Similar to the feed analysis, the surface of nest eggs from hens consuming treated feed showed reduced presumptive aerobic bacteria and tended to have less fungi contamination. Broiler offspring mortality tended to be reduced when obtained from hens consuming treated feed, especially during late laying periods. Our results indicate that treating broiler breeder hen feed with a formaldehyde-based sanitizer reduced the microbial load of feed and eggs, and positively impacted the quality and livability of the hatched chicks.